(untitled) (Libellarium: journal for research in the field of information and related sciences, 2024)
Purpose. The purpose of this article is to analyse the long-term consequences of the COVID-19 pandemic on the cultural offerings of museums in Split, with a focus on how marketing strategies have contributed to transforming a challenging time into an opportunity to improve public services and optimise management. Approach/methodology/design. The study employs qualitative research methods. Following the collection of secondary data on the cultural offerings of museums in Split before and after the pandemic, five in-depth interviews were conducted using a semi-structured questionnaire with museum directors who had agreed to participate in the study. Afterwards, the study gathered and compared the volume of activity before and after the pandemic on the social media accounts of the selected museums. Findings. The research on the secondary data and interviews reveals that after the initial shock caused by restrictions on movement of people during the lockdown period, there was a significant reduction in activity of the museums which triggered a strong reaction in management. Their search for solutions to overcome the difficulties fostered the development of ideas and strategies that resulted in meaningful changes in the way the cultural offerings of museums in Split were delivered. In particular, the research has found that the COVID-19 pandemic has (1) increased the online offerings to reach a wider audience (especially abroad) and (2) heightened public engagement with digital technologies to access cultural content in museums. Research limitations/implications. While the five interviews provide valuable insights from museum directors who represent a significant portion of Split’s cultural landscape, extending the research to include other museums and analysing the perspectives of visitors would offer a more comprehensive understanding. Practical implications. Analysing the changes and successful innovations introduced after the pandemic could encourage museums world-wide to adopt new technologies. The pandemic has underscored the importance of social media for improving the ability of museums to communicate with the public, reaching new potential visitors and enriching cultural offerings with more engaging experiences. Social implications. This research has highlighted how marketing has supported museums’ ability to react and adapt to the needs of management and visitors during a crisis. The identified strategies can act as guidelines for other cultural institutions, including libraries, to address similar challenges effectively. Originality/value. To the best of the authors’ knowledge, this research represents a rare attempt of examining the long-term impact of the pandemic on the operations of cultural (information) institutions such as museums and libraries.